AKTUALISASI PERAN MAHASISWA MAGANG PKM DALAM OPTIMALISASI FUNGSI HUMAS GUNA MEMBANGUN KOLEGIALITAS KERJA DI DINAS TENAGA KERJA DAN TRANSMIGRASI PROVINSI SUMATERA SELATAN - Mas Alvin Gemilang Arista (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Harmonious working relationships between employees are the main pillar in supporting bureaucratic effectiveness and the quality of public services in government agencies. The Community Service Program (PKM) integrated with internship activities aims to provide technical assistance and strengthen internal communication governance through optimizing the Public Relations function at the Manpower and Transmigration Office of South Sumatra Province. The implementation method uses a qualitative descriptive approach based on a structured participatory assistance scheme by implementing students from March to April 2026. Intervention activities focused on three main programs, namely the reconstruction of information dissemination flows, assistance with internal communication media mixes, and mitigating sectoral barriers (silo mentality). The results of the activities show that the actualization of the internship student work program successfully optimized the role of Public Relations as a communication bridge (boundary spanner) that synchronizes leadership directives to employees through the utilization of a media mix, such as the implementation of structured coordination meetings, digital-based circular archiving, and agency communication group governance. These tactical interventions have proven effective in reducing operational and structural barriers, particularly overlapping understandings (message distortion) and delays in information flow due to high operational workloads. It can be concluded that strengthening the role of Public Relations through this student internship service scheme can create a supportive, adaptive, and conducive internal communication climate for improving the collective performance of government agencies.